Decadal‐scale meridional shift of the typhoon recurvature latitude over five decades. (15th January 2016) - Nakano, S.; Ito, K.; Suzuki, K.; Ueno, G.
ABSTRACT: In this study, long‐term variations of typhoon trajectory patterns were analysed via the Gaussian process regression technique. Since typhoon trajectory patterns affect the risks of typhoon‐related hazards, such changes are important when developing plans to reduce those risks. Herein, long‐term variations in typical typhoon trajectory patterns were analysed simultaneously with seasonal variations. The results indicate decadal or longer meridional oscillations of typhoon recurvature points that are distinguishable from seasonal variations. Additionally, a correlation between typhoon recurvature latitudes and long‐term trends of the El Niño Southern Oscillation (ENSO) after 1990 was observed, even though this correlation appeared to be poor before 1990. Background wind field variations were also found to be consistent with those of the typhoon latitude recurvature after 1990, but the correspondence was, again, poor before 1990. These results suggest that for at least the two decades after 1990, the typhoon recurvature latitude was associated with a long‐term oscillation mode, such as the long‐term trends of the ENSO. The poor correlation before 1990 might be due to the fact that meridional variations of the typhoon recurvature latitude were primarily related to central Pacific rather than the eastern Pacific warming. However, further investigation will be necessary to attain a conclusive answer.